Diffusion Tensor Imaging Observation of Frontal Lobe Multidirectional Transcranial Direct Current Stimulation in Stroke Patients with Memory Impairment. (26th March 2022) - Hua, Hualiu; Zhang, Baixiang; Wang, Xiuling; He, Yixian; Lai, Mengting; Chen, Ninghua; Liu, Juan
Abstract : Stroke is a group of diseases caused by the sudden rupture or blockage of blood vessels in the brain that prevent blood from flowing into the brain, resulting in brain tissue damage and dysfunction. Stroke has the characteristics of high morbidity, high disability, and high mortality. To investigate the effect of multidirectional transcranial direct current stimulation (tDCS) of the prefrontal lobe in stroke memory disorder. We evaluated 60 patients with poststroke memory impairment who underwent magnetic resonance diffusion tensor imaging (DTI) during their admission to our hospital between January 2018 and December 2020. The patients were divided into the prefrontal group ( n  = 15), dorsolateral group ( n  = 15), prefrontal + dorsolateral group ( n  = 15), and pseudostimulation group ( n  = 15). Assessments using the Rivermead Behavioral Memory Test (RBMT), Montreal Cognitive Assessment Scale (MoCA), Lovingston Occupational Therapy Cognitive Scale (LOTCA), and frontal lobe fractional anisotropy (FA) were performed before and after treatment. The RBMT, MoCA, and LOTCA scores in the prefrontal + dorsolateral group were significantly higher than those in the dorsolateral, prefrontal, and sham groups (all P < 0.05 ). The posttreatment FA value of the frontal lobe was significantly higher in the prefrontal + dorsolateral group than in the dorsolateral, prefrontal, and sham stimulation groups (all P < 0.05 ). The FA value of the frontal lobe was significantly lower in patients with severe memory impairment than in patients with mild-moderate memory impairment (P < 0.05 ). The area under the receiver operating characteristic curve was 0.801 (95% CI: 0.678–0.925, P < 0.05 ), and the optimal cut-off value was 0.34, with a sensitivity and specificity of 81.60% and 72.70%, respectively. Prefrontal lobe + dorsolateral tDCS is beneficial in the treatment of post-stroke memory impairment. The DTI FA value can be useful in determining the degree of memory impairment.